Does price disclosure in pharmaceutical advertising result in price transparency? Evidence from a randomized experiment - Ilene L. Hollin; Jennifer Gerard Ball (Elsevier, 2022)
Background: Policies that mandate list price disclosure in direct-to-consumer pharmaceutical advertising (DTCPA) cite price transparency among the benefits. The expectation is that price transparency will lead to changes in consumer behavior that will ultimately lower healthcare costs. Objective: The objective of this study was to assess the impact of price transparency on perceived level of information and consumer behaviors, specifically intentions to seek treatment and intentions to comparison shop. Methods: A nine-arm randomized experiment was conducted to expose respondents to television advertisements for prescription drugs that varied by price disclosure type (no price/control, list price only, or price plus, which disclosed the list price and typical out-of-pocket cost) and indicated condition (deep vein thrombosis/pulmonary embolism [DVT/PE], diabetes, or rheumatoid arthritis [RA]). The sample was recruited from US adult members of the nationally representative Amerispeak online panel. Results: The sample included 2138 respondents. For ads featuring prescription drugs for DVT/PE, findings provide no evidence of an impact from price disclosure on perception of sufficient information. For ads for prescription drugs for diabetes, there was no evidence of an impact from list price only, but the price plus group was more likely than the control group to report the ad provided sufficient information (OR = 2.475). For ads for RA prescription drugs, both the list price only group (OR = 3.380) and price plus group (OR = 2.720) were more likely to report sufficient information than the control. Findings provide no evidence of an impact from price disclosure on consumer behaviors (i.e., intention to seek treatment or intention to comparison shop). Conclusions: Mandatory DTCPA list price disclosure may not be the most effective tool for improving price transparency and affecting consumer behavior.